Clostridial Necrotic Enteritis in Poultry - Natalia, Lily (Indonesian Animal Sciences Society, 2004)
Necrotic enteritis caused by Clostridium perfringens type A and C has been found in poultry flocks in Indonesia or throughout the world for many years. The disease is sometimes not recognized and often underestimated. Clostridium perfringens normally live harmlessly in the gut or intestines of healthy chickens, but a trigger factor that tips up the balance in favour of the clostridia) bacteria, allowing them to proliferate, produce toxin and cause the disease. Proliferation of Cl. perfringens or production of the alpha toxin may be enhanced by component present in chicken diets, or the diets may inactivate infestinal digestive enzymes, thereby decreasing the degradation of alpha toxin. In poultry, the disease is manifested as haemorrhagic and necrotic lesions in the gut wall, cholangiohepatitis, as well as increased mortality. Beside the clinical manifestation, subclinical clostridia) necrotic enteritis associated with impaired feed conversion and retarded or poor growth is usually found in the field. A number factors predisposing to the development of necrotic enteritis are physical factors which damage the gut lining (coccidiosis, intestinal worms, etc.), feed composition, changes in nutrient density or protein levels, and immunosuppresion which reduces resistance to gut infections . Impaired feed conversion, reduced live weight at slaughter and increased condemnation percentage were major cases of production losses associated with necrotic enteritis. Presently, the prevalence of necrotic enteritis appears to be increasing and pose a serious health problem which is responsible for significant economic losses . Prevention of necrotic enteritis requires a delicate balancing act to control those factors that collectively are responsible for the disease. Antibiotic, prebiotic, competitive exclusion, enzyme preparation, imunisation, mineral and vitamin supplements have been used in poultry for controlling necrotic enteritis. Key words: Clostridial necrotic enteritis, Clostridium perfringens, toxin, chicken